Bubble swarm characteristics in a bubble column under high gas holdup conditions. (10th January 2017) - Parisien, Valois; Farrell, Alixia; Pjontek, Dominic; McKnight, Craig A.; Wiens, Jason; Macchi, Arturo
Abstract: Local bubble characteristics were measured using a novel monofibre optical probe manufactured for elevated pressures and high gas holdups. The objective of this study is to test the performance of the optical probe, as well as to investigate the impact of operating conditions on bubble characteristics in a bubble column when operating under high gas holdup conditions. Experiments were conducted in a 101.6 mm diameter column operating at pressures up to 6.5 MPa. A 0.5 wt% aqueous ethanol solution was used in this study to simulate high gas holdups observed in many industrial reactors containing liquid mixtures with surface-active compounds. The probe struggled to detect all the bubbles due to significant bubble size reduction and non-rectilinear bubble rise. However, successfully detected bubbles were deemed representative of the mean bubble rise velocity as indicated by the dynamic gas disengagement technique. Global gas holdup profiles in conjunction with the drift flux analysis showed that pressure does not have a significant impact at elevated liquid flow rates as bubbles tend to follow the convective current of the liquid. Relatively narrow chord length distributions were observed, where 90% of the bubbles were 1.0 mm or less. The energy dissipated through the gas–liquid distributor plate was shown to have a significant impact on the initial bubble size generated and high gas holdups were also achieved at atmospheric pressure by varying the open-surface area of the distributor. Highlights: Rise velocities and chord lengths measured using a novel monofiber optical probe. High gas holdup conditions achieved with elevated pressure and surfactant addition. Narrow chord length distributions where 90% of the bubbles were 1.0 mm or less. Matching energy dissipation among distributor designs achieved similar gas holdups.